Notes on Claudioperla tigrina (Klapálek) in Ecuador (Plecoptera: Gripopterygidae) - Stark, Bill P. (Illiesia, 2012)
The first adult specimens of Claudioperla from the Republic of Ecuador are described from light and scanning electron microscopy. Males are compared with existing descriptions of the only currently accepted species, C. tigrina (Klapálek), and the known Ecuadorian distribution is summarized.
Keywords: entomology; Gripopterygidae; Claudioperla; Plecoptera; Ecuador; new records